(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines al-Hakim al-Tirmidhi’s views on tafsir (exegesis) and ta’wil (interpretation) as reflected in his work “Tahsil nazair al-Qur’an.” It shows that al-Tirmidhi consistently distinguishes between tafsir an explanation supported by a decisive proof such as a Qur’anic verse and ta’wil, the selection of the most fitting of a word’s possible meanings. Through an analysis of the five “aspects” (wujuh) that al Tirmidhi assigns to the word ta’wil, and a comparison with the usage of Imam al-Maturidi in “Ta’wilat ahl al-sunna,” the article argues that, for al-Tirmidhi, the “aspects” of a Qur’anic word are directly bound up with the process of ta’wil, and that “Tahsil nazair al Qur’an” constitutes, in effect, an exposition of the methodology of ta’wil and a refutation of those who reject the interpretation of the Qur’an’s ambiguous (mutashabih) verses.